MALAYSIA – INDONESIA: IN THE VORTEX OF INTERPRETATION - Sulistiyono, Bambang B; Hjaazi, Mohd Zaidi (Feb Universitas Dirgantara Marsekal Suryadarma, 2019)
Malaysia and Indonesia are two countries with a relationship that is very unique. Its society has established kinship long before the two countries was formed, which resulted similarities in each other’s culture and customs. Both countries also play a very important role in associations of the Southeast Asian nations that is accommodated through the ASEAN forum. However, the relationship between Malaysia and Indonesia have not always been great, sometimes it touches the lowest state and at other times at the most harmonious. The Realist and Liberalist theory applies in studying relations between these two countries. Although waves of problems coming and going may occur naturally, plenty of formal efforts has also been done by both governments. There are three interesting time periods in this study; the relationship period most bitter (1963-1966), the most harmonious relationship period (1968-1982), and the period of friendly but tense relations (1983-2010). Assessment of the two countries’ relationship dynamics is done through in qualitative approach with comparative analaysis and supported by the